Morfotektonika rejonu Zielonej Góry = Morphotectonics of Zielona Góra region - Markiewicz, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Paper presents characteristic of Zechstein salts layers which occur in deeper foundation of Zielona Góra region. Author suggests that variation of salt thickness are connected with activity of continental glaciers and notices characteristic relation between thickness of salt layer and contemparary morphology of area surface.
Keywords: glacitektonika; morfotektonika; Zielona Góra; glaciotectonics; morphotectonics